Oral Antiplatelet and Anticoagulant Agents in the Prevention and Management of Ischemic Stroke (Current Pharmaceutical Design, 2017)
Despite numerous advances over the last 50 years, stroke continues to be a leading cause of death and disability worldwide. The treatment and prevention of stroke has undergone extensive study, and significant advances in medical management have occurred within the past decade principally with the development of new classes of orally active anticoagulant drugs. Here we review these recent breakthroughs and the varying roles of anticoagulants and antiplatelet agents in the prevention and management of different ischemic stroke subtypes, as well as describe the benefits and ongoing challenges to incorporating the novel oral anticoagulants (NOACs) into clinical management guidelines. Current guidelines recommend (a) administration of the antiplatelet agent aspirin in the acute management of ischemic stroke, (b) antiplatelet therapy - aspirin, clopidogrel, dypiridamole - in the secondary prevention of noncardioembolic (large artery atherosclerosis) ischemic stroke, and (c) anticoagulants - warfarin and the NOACs - in the secondary prevention of cardioembolic (atrial fibrillation related) ischemic stroke. In phase III clinical trials of the NOACs, dabigatran 150mg BID and apixaban 5mg BID were superior to warfarin in the prevention of stroke/systemic embolism while rivaroxaban 20mg QD demonstrated noninferiority. Both dabigatran and rivaroxaban had similar rates of major bleeding as warfarin but apixaban showed significantly reduced incidence of this complication. As application of novel anticoagulant agents increases, with concomitant study in a variety of clinical settings; their promise in reducing the incidence of stroke, as well as that of therapeutic complications related to warfarin, should be further elaborated.
Keywords: warfarin